2016
DOI: 10.1186/s12870-016-0712-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, linkage disequilibrium, population structure and construction of a core collection of Prunus avium L. landraces and bred cultivars

Abstract: BackgroundDepiction of the genetic diversity, linkage disequilibrium (LD) and population structure is essential for the efficient organization and exploitation of genetic resources. The objectives of this study were to (i) to evaluate the genetic diversity and to detect the patterns of LD, (ii) to estimate the levels of population structure and (iii) to identify a ‘core collection’ suitable for association genetic studies in sweet cherry.ResultsA total of 210 genotypes including modern cultivars and landraces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
86
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 56 publications
15
86
0
1
Order By: Relevance
“…The DAPC method is being used instead of STRUCTURE software as it does not require that populations should be in HW equilibrium. In addition, it can handle large sets of data without using parallel processing software [59]. Deperi et al [60] have mentioned that DAPC analysis can divide the population into well-defined clusters associated with provenance, ploidy, taxonomy, and breeding program of genotypes related to their genetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…The DAPC method is being used instead of STRUCTURE software as it does not require that populations should be in HW equilibrium. In addition, it can handle large sets of data without using parallel processing software [59]. Deperi et al [60] have mentioned that DAPC analysis can divide the population into well-defined clusters associated with provenance, ploidy, taxonomy, and breeding program of genotypes related to their genetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…The r 2 ‐value has dropped below 0.2 at approximately 1,000 kb in a collection of 1,240 peach accessions (Micheletti et al ). Therefore, it is clear that LD decays more rapidly in cross‐pollinated species than in self‐pollinated species as the recombination frequency is higher in cross‐pollinated species (Campoy et al ). In summary, this study has revealed that LD decays very rapidly in the self‐incompatible apple.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted 20 iterations to assess the stability in detection of the number of clusters. To prevent overfitting when conducting the DAPC, the number of principal components to retain was determined with a cross-validation approach as implemented by the function xvalDapc() (e.g., Campoy et al, 2016;Van Cann, Virgilio, Jordaens, & De Meyer, 2015;Virgilio et al, 2015) with 100 repetitions.…”
Section: Discriminant Analysis Of Principal Componentsmentioning
confidence: 99%